Pyrolysis kinetics and reaction mechanism of expandable polystyrene by multiple kinetics methods. (20th February 2021) - Zhang, Wenlong; Zhang, Juan; Ding, Yanming; He, Qize; Lu, Kaihua; Chen, Haiyan
Abstract: Expandable polystyrene (EPS), as an industrial material extensively used for energy saving in building exterior insulation system, helps to decrease the energy consumption from buildings. However, such material, because of its flammability, still has the potential risk of resulting in a large number of fire accidents. Pyrolysis is deemed as an essential stage before combustion, so studies on pyrolysis can lay a solid foundation for understanding the thermal behavior of EPS before combustion. Nevertheless, with a growing number of undegradable EPS waste that results in environmental issues, some measures must be taken to dispose of such waste. In this case, pyrolysis technology is gradually employed to convert polymer wastes into fuel or chemical feedstock. Therefore, it is necessary to investigate the pyrolysis of EPS. To obtain the pyrolysis kinetics and mechanism of EPS, thermogravimetric analysis was performed at wider heating rates in the air, and the activation energy was estimated by adopting commonly-used model-free methods (including Flynn-Wall-Ozawa, Kissinger-Akahira-Sunose, Senum-Yang, Starink, and Advanced Vyazovkin method). Then, a reaction mechanism was established and the kinetic parameters were calculated by Coats-Redfern and masterplots methods. Finally, the Málek method was applied for a reconstruction of the experimental kinetic model of EPS pyrolysis. Results indicated that the pyrolysis of EPS might be well characterized by employing a reconstructed reaction function dα/dt  =  2.18  ×  10 8 exp(-1.38  ×  10 5 /RT)α 0.0309 (1-α) 0.7689 . Furthermore, the results of pyrolysis analysis, especially the reaction function of such a reaction mechanism, could provide guidance for large-scale fire simulation of EPS and disposal of EPS waste, thus contributing to environmental sustainability and cleaner production of fuel. Highlights: The pyrolysis kinetics of expandable polystyrene (EPS) is studied in the air. Multiple model-free and model-fitting methods are coupled with the Málek method. The reaction mechanism of EPS is established and kinetic parameters are estimated. The kinetic model of EPS is reconstructedby employing the Málek method.